Pengaruh Desentralisasi Fiskal, IPM, Panjang Jalan Terhadap Kemiskinan di Papua - Anita Kusumawati; Lilis Siti Badriah; Agus Arifin (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Poverty is an important problem for each country, both developed and developing countries, including Indonesia. The government continues to strive to reduce poverty levels through various mechanisms such as fiscal decentralization, human capital development and infrastructure development. In Indonesia, Papua is an area that has the highest poverty conditions in Indonesia. This research uses panel data consisting of the provinces of Papua and West Papua for the period 2008-2022. The analysis technique used is panel data regression. The results of the analysis show that special autonomy funds have a positive effect on poverty, HDI and regional spending have a negative effect on poverty. DBH, DAU, DAK, and road length have no effect on poverty levels. The implication of this research is the need to optimize the realization of transfer funds and increase infrastructure development so that it can reduce poverty levels.